Pengaruh Merk, Gaya Hidup, Word of Mouth Terhadap Keputusan Pembelian Lip Cream Matte Implora di Toko Ivanna Kosmetik Malang (Studi Pada Konsumen di Toko Ivanna Kosmetik Malang) - Anjar Surya Ningsih; Nurhajati Nurhajati; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The effect of Brand Image, Life Style, Word of Mouth on purchasing decisions of Lip Cream Matte Implora at the Ivanna cosmetic Malang store,  a study on consumers at the Ivanna cosmetic Malang store. This study uses a quantitative approach which uses the malhotra formula in order to determine the sample the calculation results of the malhotra formula, the number of samples is 75. in analyzing, normality test, hipothesis testing, multiple linear regression test and adjusted R² coefficient tes.  of this study are Brand Image, Life Style, Word of Mouth influence purchasing decisions simultaneously Keywords: Brand Image, Life Style, Word of Mouth, Purchase Decision